USE OF CARVACROL HELPS MAINTAIN POSTHARVEST QUALITY OF RED GLOBE TABLE GRAPE - Z. Babalık1; C. E. Onursal; D. Erbaş; M. A. Koyuncu (Journal of Animal and Plant Sciences, 2020)
In this paper, role of carvacrol vapour on postharvest grape quality was studied. For this aim, 100, 250, 500 and 1000 μl carvacrol absorbed gauzes were placed near the clusters for treatments. Besides, pads generating sulfur dioxide (SO2) and control grapes were also used for comparison. All clusters were packed with modified atmosphere packaging (MAP) and stored at 1 oC and conditions of 90±5% relative humidity (RH) in darkness for 120 days. Some quality characteristics were examined at 20 days intervals. As a result, all concentrations of carvacrol delayed the changes in titratable acidity (TA) and firmness, and reduced weight loss at the end of storage. In addition, the fungal decay also reduced dependent on the highest carvacrol concentration. No deterioration was observed during the 40th day of storage treated with all carvacrol treatments and SO2. All the treated grapes sampled on 120th day of storage had lost marketability. Also in our study, carvacrol was found to be more successful in terms of taste than control and SO2 application. The results showed in this study that carvacrol could be used as an innovative tool to maintain postharvest quality during table grape storage, as alternative to use of SO2.
Keywords: Essential oil; carvacrol; Red Globe; quality; postharvest treatment